2017 IEEE Conference on Communications and Network Security (CNS) 2017
DOI: 10.1109/cns.2017.8228685
|View full text |Cite
|
Sign up to set email alerts
|

Open-source flexible packet parser for high data rate agile network probe

Abstract: The development of a network centered life has increased overall data rates in core networks. Thus, data centers face the challenge to provide always more services at higher data rates while reacting quickly to complex failures and more powerful attacks thanks to efficient network forensics. Moreover, Software-Defined Networking (SDN) becomes a standard which offers agility but also requires forensic devices able to handle multiple configurations. Although conventional software probes are programmable and thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…As shown in Table 2, our work, denoted as "Our work 1 " was implemented on the Xilinx Ultrascale+ FPGA series platform. Despite [14,28] using more advanced FPGA devices than ours, our results exhibit a significant reduction in processing latency. To ensure a fair comparison with [17], we recompiled our system on the Xilinx Virtex-7 XCVH580T FPGA platform used in [17], denoted as "Our work 2 " in the table.…”
Section: Performance Analysismentioning
confidence: 61%
See 2 more Smart Citations
“…As shown in Table 2, our work, denoted as "Our work 1 " was implemented on the Xilinx Ultrascale+ FPGA series platform. Despite [14,28] using more advanced FPGA devices than ours, our results exhibit a significant reduction in processing latency. To ensure a fair comparison with [17], we recompiled our system on the Xilinx Virtex-7 XCVH580T FPGA platform used in [17], denoted as "Our work 2 " in the table.…”
Section: Performance Analysismentioning
confidence: 61%
“…Based on the waveform obtained through the cocotb simulation tool, as shown in Figure 15, it can be observed that a total of nine clock cycles were required from the start of parsing to the completion of parsing, resulting in the output of PHV. Table 2 compares the proposed parser design with several previous designs [14,17,28]. The IXIA testers used a custom frame structure to generate traffic, as shown in Figure 16, to set up an Ethernet-IPV6-UDP-based parsing path and analyze the latency.…”
Section: Performance Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The performance of software vRouters is limited by packet parsing. In general, the software performance of packet parsing with 1CPU core is under 7 Mpps [10]. On the other hand, a paper [11] reported that "300 Mpps has been achieved by software only on one server."…”
Section: B Network Acceleration Technologiesmentioning
confidence: 99%
“…Big player like amazon and Intel have included FPGAs in their products and services. Amazon uses FPGAs for cloud computing [10], [11], [12] while intel has become a key player in the FPGAs industry with their purchase of Altera [13]. These points to the growing potentials of FPGAs in the electronics industry.…”
Section: List Of Figuresmentioning
confidence: 99%